Search Intensity, Job Advertising, and Efficiency - Pissarides, Christopher A. (Journal of Labor Economics, 1984)
This paper demonstrates that if both firms and workers search the other side of the market for job matches the equilibrium rate of unemployment is likely to be too high. Both sides ignore a positive externality of their search: when they establish a job match they remove from the market a job searcher, so they save society his search costs. I show that there is no feasible wage rate that can internalize this externality under fairly weak restrictions on the technology of search.